ANALISIS YURIDIS MENGENAI PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN SKINCARE SHARE-IN JAR TANPA IZIN EDAR YANG DIJUAL SECARA ONLINE - Asrimutia, Evicennia; Rachmawati, Rachmawati; Karlina, Dina (Faculty of Law, Universitas Tanjungpura, 2025)
Abstract Technological developments affect international trade and e-commerce. Consumer protection is very important for Share In Jar skincare products without a distribution permit sold online to provide legal certainty. This research examines consumer protection against the circulation of Share In Jar skincare products without a distribution permit sold online, combining preventive and repressive legal approaches.The formulation of the problem that is the focus of the study is